Chromium supplementation can alleviate negative effects of heat stress on egg production, egg quality and some serum metabolites of laying Japanese quail - Şahin, Kazım; Ozbey, O; Onderci, M; Cikim, G; Aysondu, MH (Elsevier Science Inc, 2002)
This study was conducted to determine the effects of Cr (chromium picolinate, CrPic) supplementation at various levels (0, 200, 400, 800 or 1200 mug/kg of diet) on egg production, egg quality and serum concentrations of insulin, corticosterone and glucose in laying Japanese quail (Coturnix coturnix japanica) reared under conditions of heat stress (32.5degreesC). Laying Japanese quail (n = 150; 45 d old) were divided into five groups of 30 birds. The quail were fed either a control diet containing 965 mug Cr/kg diet or the control diet supplemented with 200, 400, 800 or 1200 mug of Cr/kg diet. Increased supplemental chromium increased body weight (P = 0.05, linear), feed intake (P = 0.05, linear), egg production (P = 0.01, linear) and also improved feed efficiency (P = 0.01, linear). Increased supplemental chromium linearly increased egg weight (P = 0.01), eggshell thickness, egg specific gravity (P = 0.05) and Haugh unit (P = 0.01). Serum insulin concentration increased linearly (P = 0.01), whereas corticosterone and glucose concentration decreased linearly (P = 0.05) as dietary chromium increased. The best results were obtained with 1200 mug Cr/kg diet, and chromium supplementation at such a level can be considered to be protective management practice in a quail diet, reducing the negative effects of heat stress.
Keywords: chromium; eggs; insulin; corticosterone; Japanese quail